Childhood maltreatment, vulnerability characteristics and adult incident common mental disorders: 3-year longitudinal data among >10, 000 adults in the general population. (June 2019) - ten Have, Margreet; de Graaf, Ron; van Dorsselaer, Saskia; Tuithof, Marlous; Kleinjan, Marloes; Penninx, Brenda W.J.H.
Abstract: Childhood maltreatment (CM) is a strong predictor of incident (first-onset and recurrent) mental disorders in adulthood. However, less is known about underlying mechanisms and moderators of these associations. This study examines to what extent vulnerability characteristics (low social support, negative life events, parental psychopathology, neuroticism, history and comorbidity of mental and physical health) contribute to the impact of CM on adult psychopathology. Data from two general population cohorts – the first and second Netherlands Mental Health Survey and Incidence Studies – were combined into one dataset (N = 10, 065). CM (emotional, psychological, physical or sexual abuse before the age of 16) and vulnerability characteristics were assessed with a structured face-to-face interview. First-onset and recurrent mental (mood, anxiety, substance use) disorders were assessed using the Composite International Diagnostic Interview. CM doubled the risk of developing a first-onset or recurrent mental disorder at three-year follow-up (OR = 2.08). CM was not only directly connected to incident mental disorders, but also indirectly through vulnerability characteristics. Several vulnerabilities, in particular low social support, parental psychopathology, prior mental disorders and neuroticism, moderated the relationship between CM and adult mental disorders, indicating that these vulnerability factors had a greater effect on incident mental disorders among people with childhood abuse. As not all adults with a history of CM develop mental disorders, these mediating and moderating risk factors might help identify adults with a history of maltreatment who could benefit from preventive interventions.